Ethnicity, Social Capital and the Internet - Parker, David; Song, Miri (SAGE Publications, 2006)
This article explores web sites developed to express the interests and experiences of young Chinese people in Britain. Drawing on content analysis of site discussions and dialogues with site users, we argue these new communicative practices are best understood through a reworking of the social capital problematic. Firstly by recognising the irreducibility of Internet-mediated connections to the calculative instrumentalism underlying many applications of social capital theory. Secondly, by providing a more differentiated account of social capital. The interactions we explore comprise a specifically “second generation” form of social capital, cutting across the binary of bonding and bridging social capital. Thirdly judgement on the social capital consequences of Internet interactions must await a longer-term assessment of whether British Chinese institutions emerge to engage with the wider polity.